SOSIALISASI PENGENALAN WAKAF TERHADAP IBU-IBU PENGAJIAN MASJID AL-ISLAMI JALAN AKBP H. UMAR ARIO KEMUNING KOTA PALEMBANG - Saprida Saprida; Zuul Fitriani Umari (AKM, 2021)
This community service activity discusses the introduction of waqf from the meaning of waqf, the terms and conditions of waqf, the legal basis for waqf, various kinds of waqf, waqf objects, waqf for moving objects in the perspective of Islamic law and waqf for moving objects in the form of currency. Waqf is the use of assets to benefit from by maintaining the essence of the object and deciding the wakif's right to utilize the assets. Wakif may not do anything with the assets being donated. The purpose of this community service activity is to provide an introduction to waqf for women reciting the Al-Islami Ario Kemuning mosque in Palembang with the hope that the socialization participants can understand the benefits of giving waqf fairly and correctly. Socialization participants can also know that waqf can prosper the community and get a reward for the wakif.